Analysis of neural crest-derived clones reveals novel aspects of facial development - Kaucka, Marketa; Ivashkin, Evgeny; Gyllborg, Daniel; Zikmund, Tomas; Tesarova, Marketa; Kaiser, Jozef; Xie, Meng; Petersen, Julian; Pachnis, Vassilis; Nicolis, Silvia K; Yu, Tian; Sharpe, Paul; et al. (Science advances, 2016)
Cranial neural crest cells populate the future facial region and produce ectomesenchyme-derived tissues, such as cartilage, bone, dermis, smooth muscle, adipocytes, and many others. However, the contribution of individual neural crest cells to certain facial locations and the general spatial clonal organization of the ectomesenchyme have not been determined. We investigated how neural crest cells give rise to clonally organized ectomesenchyme and how this early ectomesenchyme behaves during the developmental processes that shape the face. Using a combination of mouse and zebrafish models, we analyzed individual migration, cell crowd movement, oriented cell division, clonal spatial overlapping, and multilineage differentiation. The early face appears to be built from multiple spatially defined overlapping ectomesenchymal clones. During early face development, these clones remain oligopotent and generate various tissues in a given location. By combining clonal analysis, computer simulations, mouse mutants, and live imaging, we show that facial shaping results from an array of local cellular activities in the ectomesenchyme. These activities mostly involve oriented divisions and crowd movements of cells during morphogenetic events. Cellular behavior that can be recognized as individual cell migration is very limited and short-ranged and likely results from cellular mixing due to the proliferation activity of the tissue. These cellular mechanisms resemble the strategy behind limb bud morphogenesis, suggesting the possibility of common principles and deep homology between facial and limb outgrowth.
Keywords: dánio pruhované; Animals; Morphogenesis; Face; Phenotype; ektoderm; zobrazování trojrozměrné; organogeneze; Imaging, Three-Dimensional; reportérové geny; buněčné klony; buněčná diferenciace; morfogeneze; Mice; Organogenesis; Neural Crest; myši; pohyb buněk; obličej; Zebrafish; Mesoderm; mezoderm; exprese genu; Ectoderm; anatomické modely; Cell Differentiation; Clone Cells; fenotyp; zvířata; Cell Movement; Genes, Reporter; crista neuralis; Models, Anatomic; Gene Expression